Dynamics of Education in Coastal Communities: An Analysis of Limited Access and Distribution of Teachers - Desylia Widyasari; Ahmad Maghfurin; Uswatun Marhamah (Journal of Islamic Education Thought and Development, 2026)
Educational inequality remains a critical issue in marginalized coastal communities, where standardized schooling systems often fail to accommodate local socio-economic conditions. This study examines the educational challenges faced by fishing communities in Tegalsari Timur Village, Ampelgading District, Pemalang Regency, Central Java, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis involving eight key informants, including teachers and parents. Data validity was ensured through source and methodological triangulation, while analysis followed the Miles and Huberman interactive model. The findings reveal that educational disparities are driven by three interconnected factors: unequal teacher distribution due to geographic isolation, fluctuating student attendance associated with seasonal fishing activities, and limited educational infrastructure. These challenges create a mismatch between nationally standardized educational policies and the realities of coastal communities. To address these issues, participants emphasized the importance of geographically differentiated teacher incentives, flexible academic calendars aligned with local livelihood cycles, and community-based school management involving fishing households. This study introduces the concept of Coastal Pedagogical Adaptivity, which highlights the importance of institutional flexibility and community collaboration in improving educational access and participation in marginalized coastal areas. The findings demonstrate that context-sensitive educational policies are more effective than uniform approaches in addressing local needs and promoting educational equity for children in fishing communities.